2017
DOI: 10.1021/acs.analchem.7b00135
|View full text |Cite
|
Sign up to set email alerts
|

Allyl Fluorescein Ethers as Promising Fluorescent Probes for Carbon Monoxide Imaging in Living Cells

Abstract: Recently, the fluorescent detection of carbon monoxide (CO) in living cells has attracted great attention. However, due to the lack of effective ways to construct fluorescent CO probes, fluorescent detection of CO in living cells is still in its infancy. In this paper, we report for the first time the use of allyl ether as a reaction site for construction of fluorescent CO probes. By this way, two readily available allyl fluorescein ethers were prepared, which were found to be highly selective and sensitive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
103
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(104 citation statements)
references
References 39 publications
0
103
0
1
Order By: Relevance
“…Thus, the selective uorescence increase at 515 nm should be solely ascribed to the photo-mediated CO release that, in turn, activated the allyl-Flu probe through the COmediated Tsuji-Trost reaction. 58 Building on the above results, we can safely conclude that CO could be released from OM micelles under visible light irradiation.…”
Section: Photo-triggered Tandem Photochemical Reactions For Co Releasementioning
confidence: 56%
See 1 more Smart Citation
“…Thus, the selective uorescence increase at 515 nm should be solely ascribed to the photo-mediated CO release that, in turn, activated the allyl-Flu probe through the COmediated Tsuji-Trost reaction. 58 Building on the above results, we can safely conclude that CO could be released from OM micelles under visible light irradiation.…”
Section: Photo-triggered Tandem Photochemical Reactions For Co Releasementioning
confidence: 56%
“…2f). 58 In contrast, no uorescence was detected in the absence of OM micelles under otherwise identical conditions (Fig. S16a †).…”
Section: Photo-triggered Tandem Photochemical Reactions For Co Releasementioning
confidence: 91%
“…Fluorescence confocal microscopic images of endogenous CO detection due to heme stimulation in HeLa cells were also reported. [44] In continuation of these works they have also reported a naphthalimide based CO probe 1 and a coumarin based probe BTHC-CO ( Figure 5B) which showed similar but sensitive responses toward CO. [45,46] Tang and co-workers reported two probes ACP-1 and ACP-2 for the detection of CO in aqueous buffer, while the more efficient ACP-2 can sense endogenous CO inside cell in hypoxia condition. The azobenzene-BODIPY based cyclopalladated com-plex undergoes protonolysis of the PdÀ C bond and subsequently shows fluorescence due to the generation of highly emissive BODIPY-derivative ( Figure 6A).…”
Section: Fluorescent Probes For Non-targetable Co Detection In Livingmentioning
confidence: 64%
“…Subsequently, by using allyl ether instead of allylcarbonate as the protective unit and recognition site, Feng et al reported a second generation uorescein-based COresponsive uorescent probe (probe 40). 58 This probes exhibited superior stability compared to probe 39 and excellent sensing performance for CO. It is worth noting that this was the rst uorescent probe that utilized allyl ether as the reaction site for CO, which will provide more options for developing effective CO-detecting uorescent probes.…”
Section: Tsuji-trost Reactionmentioning
confidence: 99%
“…In the next few years, Feng's group reported various uorescent probes based on the Pd(0)-mediated Tsuji-Trost reaction. [57][58][59][60] In 2016, they reported a readily available uorescent probe 39 (ref. 57) based on the allyl chloroformate functionalized uorescein for the detection of CO.…”
Section: Tsuji-trost Reactionmentioning
confidence: 99%